Knowledge regarding cardiopulmonary resuscitation and its associated factors among primary care doctors in outpatient clinics in Melaka, Malaysia - Azman, Muhammad Nuaim Muhammad (2020)
Introduction: Early cardiopulmonary resuscitation (CPR) and early defibrillation are important factors in the chain of survival and doctors play crucial role as early responders in cardiac arrest cases outside of the hospital. This study aims to assess knowledge and attitude towards CPR among primary care doctors in Melaka and factors associated with having good knowledge among the doctors. Methods: This is a 12 months cross sectional study that was conducted between 10th October 2018 until 9th October 2019 using a modified questionnaire involving all Primary Health Clinics in Melaka. All doctors who fitted the inclusion and exclusion criteria were invited to participate and required to fill up the self-administered questionnaire that test their knowledge and attitude towards CPR. Results: Out of 250 respondents, 59.6% had good knowledge and 20% had positive attitude towards CPR. Among the factors studied, age (p= 0.007), duration in service (p= 0.004) and have experience performing CPR (p= 0.034) have been found to have association with good knowledge in CPR. Conclusions: Most primary care doctors in outpatient clinics in Melaka have good knowledge of CPR but have negative attitude towards it. Age, duration in service, and having performed CPR were factors that associated with good knowledge on CPR. These highlights need of exposure and training to improve knowledge of CPR among government primary health care doctors in Melaka.